A glycoproteomic approach to identify novel glycomarkers for cancer stem cells. Issue 24 (9th May 2016) - Sawanobori, Atsuko; Moriwaki, Kenta; Takamatsu, Shinji; Kamada, Yoshihiro; Miyoshi, Eiji
Abstract : Most cancers consist of heterogeneous populations of cells with substantial differences in tumorigenicity. Cells that possess self‐renewal and tumor‐initiating properties are often called cancer stem cells (CSCs). Since CSCs underlie tumor recurrence and metastasis and are resistant to current anti‐cancer therapies, novel therapeutic strategies to efficiently target this subset of cells are needed. Aberrant glycosylation is one of the hallmarks of cancer. Many cancer‐associated glycans have been reported to be involved in tumor progression and metastasis, and are used as tumor markers. Over the past several years, we have identified characteristic glycans on CSCs by utilizing recent advances in glycoproteomic technologies. In this review, we would like to summarize a series of our recent studies and discuss possible applications of glycomarkers for CSCs.